DL-ICE as a bridge to allogeneic transplantation in relapsed/refractory PTCL: survival outcomes and prognostic factors - Kim, Tong-Yoon; Kim, Tae-Jung; Han, Eun Ji; Min, Gi June; Cho, Seok-Goo; Jeon, Youngwoo (Frontiers in Oncology, 2024)
IntroductionPeripheral T-cell lymphomas (PTCLs) have poor outcomes in the relapsed/refractory (R/R) setting. In this study, we evaluated the efficacy of dexamethasone, L-asparaginase, ifosfamide, carboplatin, and etoposide (DL-ICE) chemotherapy followed by allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with R/R PTCLs.MethodsWe retrospectively analyzed 80 adult patients with R/R PTCLs treated with DL-ICE chemotherapy between September 2009 and March 2023. Patients achieving complete or partial remission were eligible for consolidative allo-HSCT. Overall survival (OS) and progression-free survival (PFS) were evaluated.ResultsThe overall response rate to DL-ICE was 37.5%, with 30% achieving complete remission (CR). With a median follow-up of 96.4 months, the median OS and PFS were 8.9 and 3.8 months, respectively. Seventeen patients (21%) underwent allo-HSCT, including 11 with non-CR status. The 5-year OS was significantly higher in the allo-HSCT group compared to that in the group with chemotherapy alone (64.7% vs 18.3%, p <0.001). Multivariate analysis identified advanced stage, EBV viremia, and non-CR status as poor prognostic factors.DiscussionDL-ICE chemotherapy demonstrated modest activity in R/R PTCLs. Consolidation with allo-HSCT, even in patients who do not achieve CR, resulted in long-term survival in a subset of patients. Early consideration of allo-HSCT may improve outcomes for patients with R/R PTCLs.